Teaching science and mathematics in rural area a case study of Sk Sabur, Sabah, Malaysia / Azwan Ahzran Perman - Perman, Azwan Ahzran (2021)
Teaching in rural elementary school is itself a challenge for teachers. Since rural schools generally have inferior equipment and infrastructure as opposed to urban schools, teaching technical subjects such as Science and Mathematics can be even more challenging than non-technical ones. This study attempted to understand the challenges and initiatives of teachers for teaching Science and mathematics in SK Sabur, Banggi island (Pulau Banggi), Kudat, Sabah, Malaysia. As a qualitative study, it collected data from a descriptive case study, a semi-structured interview, and observation. Through triangulation of the data and thematic analysis of the transcriptions, the study found the following themes: (I) Governmental role of education in the rural area, (II) personal sacrifices, and (III) local-based innovation and passion for teaching. All in all, it is pertinent for the government to continue improving ways to mitigate the challenges that teachers face in teaching Science and Mathematics in rural schools to ensure the delivery of quality education across all areas of the country. Future studies should include challenges of teaching in the rural area during Covid-19-lockdown and restricted movement phases